The Role and the Significance of Intellect from Farabi’s Point of View - Somayyeh Bolboli Ghadikolaaii; Hamid Parsania (اخلاق وحیانی)
The study of the relationship between intellect and ethics is one of the unavoidable philosophical discussions regarding ethics. Moreover, Farabi is also considered to be one of the most influential Muslim philosophers in the field of ethics. The present paper seeks to answer the question “what is the role and significance of intellect with regard to ethics?” To this end, first, Farabi’s perspective on the theory of intellect will be discussed. Farabi’s theory of intellect is based on the connection of human intellect with the immaterial world which is mediated by the agent intellect. Next, the concept of ethics as well as the goal of ethics, which is felicity, from Farabi’s viewpoint will be discussed and, finally, the role and significance of intellect concerning the achievement of felicity will be discussed in detail from different perspectives. It is noteworthy that, in Farabi’s school of thought, felicity is not a simple and primitive concept; rather, it is a compound concept, for the discerning of which, its relationship with other concepts such as willpower, freewill, pleasure, knowledge, instruction and correction must be clarified. Thus, following the presentation of the definition of the concept of intellect and its different kinds from Farabi’s point of view, the manner in which it will emerge and influence each of the aforementioned concepts will be specified. It will be discussed that, contrary to some of the philosophers of ethics, Farabi has considered a very significant role for intellect in ethics and he has depicted this issue through various ways and different concepts.